Inhibitory Activities of a Probiotic Bacterium (Bifidobacterium Pseudocatanulatum) on a Common Diarrheagrnic Pathogen (Salmonella Enterica) in Human - Meor Hussin, Anis Shobirin (2003)
Sixteen strains of Salmonella were isolated from clinically diagnosed diarrhea patients. They were tested against a range of antimicrobial agents, and typed by serological test and RAPD fingerprinting. All the strains have the similar pattern of antimicrobial susceptibility. The serological test has typed them into 3 serovars but the RAPD fingerprinting has classed them into 2 major clusters. Three strains of bifidobacteria were analyzed for their survival rate in human stomach condition. It showed that the ability of bifidobacteria to survive was strains dependant. Bifidobacterium pseudocatanulatum F117 and Bifidobacterium infantis can survive at pH value of human stomach after exposure for 90 minutes but not Bifidobacterium pseudocatanulatum G48. The survival of bifidobacteria was higher in the pH after meal compared to the pH before meal (fasted state). The dose effect study demonstrated, that the initial concentration of bifidobacteria would affect the duration of inhibitory activity against Salmonella. Lower initial concentration exhibit greater inhibitory activity. The inhibition of Salmonella was due to the production of acetate and lactate by bifidobacteria and the effectiveness was higher at low pH. Acetate and lactate production was excessive when the initial concentration of bifidobacteria was low due to the high growth rates, metabolism, and competition of energy sources.